Strengths and Limitations of Internet-Based Cognitive-Behavioral Treatments for Anxiety Disorders - Woods, Alexandra P; Stults, Christopher B; Terry, Rachel L; Rego, Simon A (Pragmatic Case Studies in Psychotherapy, 2017)
This commentary discusses the strengths and limitations of internet-based cognitive-behavioral treatments (ICBT) for anxiety disorders, as highlighted by the case studies described in Ciuca, Berger, and Miclea (2017), and in Schulz, Vincent, and Berger (2017). In comparing the course of treatment for patients with contrasting clinical outcomes, the authors offer insights into the many benefits and challenges of ICBT. Suggestions for improving ICBT interventions for anxiety disorders, implications for implementation and dissemination, and ethical considerations are discussed.